Advancing Leaders and Leadership: New Zealand Women in Respiratory Medicine - Yap, Elaine; Mooney, Sarah (John Wiley & sons, 2022)
The 19th century saw many notable events unfold in the history of Aotearoa New Zealand (NZ) women (wāhine), highlighting the importance of gender equality to this nation even in those early years. NZ women became the first in the world to vote in 1893. In the medical field, Grace Neill led major nursing and midwifery reforms establishing a series of state maternity hospitals ‘for mothers, managed by women and doctored by women’, whilst Dr Emily Siedeberg became the first female NZ medical graduate in 1896 (Figure 1).1 Together, they defended this innovative women-focused model from medical colleagues and tradition, creating a new care paradigm. Globally, many pioneering women in medicine shared Neill and Siedeberg's experiences of challenging societal norms that discriminate against women's rights and rise to leadership. Has the foundation laid down by these courageous, determined women paved an easier path for women today in medicine in Aotearoa NZ? This article reflects on the status of NZ women in multidisciplinary respiratory care teams including respiratory physicians, physiotherapists and nurses 125 years later.
Keywords: Leaders; Respiratory; Medicine women